A proposed online radio station in UP Mindanao designed based on formative audience research - Beltran, Honey Felomel A. (2018)
In 2016, the community of the University of the Philippines Mindanao (UP Mindanao) had their first online campus radio station called Radio Iskolar: Ang Boses ni Oble, created through an online streaming platform, Mixlr. It is atype of community radio led primarily by students. It offers the students control to the program, its content formats which is usually bounded by cultural context. It also serves as a platform for active participation, an outlet for freedom of expression, and a venue for community service (Trenholm, 2004). The result of the study shows that the respondents have high level of knowledge, perception, and attitude towards online radio. Majority of the respondents preferred Music, News, Radio Discussions, and Radio talks for the radio program formats. For the content, majority are interested to know about Health, Education, Human rights, Research, issues about the university, the government, the society, and politics. The programming plan for the online radio station is designed based on the results of the study, it will serve as a platform to encourage participation and involvement in the community-building process and exercise public service. This will also serve as laboratory to develop the talents and skills of the students in radio broadcasting. Thus, this study proposed to design an online radio station in UP Mindanao based on the formative audience research conducted by the researcher.